2007
DOI: 10.1375/twin.10.5.683
|View full text |Cite
|
Sign up to set email alerts
|

Review of Twin and Family Studies on Neuroanatomic Phenotypes and Typical Neurodevelopment

Abstract: This article reviews the extant twin studies employing magnetic resonance imaging data (MRI), with an emphasis on studies of populationbased samples. There have been approximately 75 twin reports using MRI, with somewhat under half focusing on typical brain structure. Of these, most are samples of adults. For large brain regions such as lobar volumes, the heritabilities of large brain volumes are consistently high, with genetic factors accounting for at least half of the phenotypic variance. The role of geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
72
3

Year Published

2008
2008
2013
2013

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 55 publications
9
72
3
Order By: Relevance
“…>50%) as found here and reported previously. It is also considerably lower than that reported for lobar and overall brain volumes, and regional grey and white matter volumes, which in general have a high heritability (reviewed by Schmitt et al, 2007), as indicated here for total grey matter volume. However, our heritability estimates for task-related brain activation are comparable in magnitude to a recent study in which genetic influences accounted for 38% of the variance in activation of the dorsal anterior cingulate cortex during an interference task (Matthews et al, 2007).…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…>50%) as found here and reported previously. It is also considerably lower than that reported for lobar and overall brain volumes, and regional grey and white matter volumes, which in general have a high heritability (reviewed by Schmitt et al, 2007), as indicated here for total grey matter volume. However, our heritability estimates for task-related brain activation are comparable in magnitude to a recent study in which genetic influences accounted for 38% of the variance in activation of the dorsal anterior cingulate cortex during an interference task (Matthews et al, 2007).…”
Section: Discussioncontrasting
confidence: 55%
“…Two recent twin studies using fMRI, the first focussing on sadness in a reasonably large sample (104 pairs) of 8-year-old twins (Côté et al, 2007), and the second using an interference processing task and a small sample of 20 female twin pairs (Matthews et al, 2007), suggest that there may be a modest, if any, genetic influence on neural activation, as captured by fMRI, and that the genetic contribution to individual differences in task-related brain activation may be both task specific and regionally variable. This is in contrast to twin studies using structural MRI that indicate there is a strong influence of genes on the volumes of brain structures, and on grey and white matter subvolumes; heritability of subcortical regions has been less well studied showing lower and more variable heritabilities (reviewed by Schmitt et al, 2007).…”
Section: Introductionmentioning
confidence: 81%
“…However, the latter might be partly due to reduced statistical power in the smaller subgroup of MZ twins (40 MZ vs. 72 DZ). Because heritability estimates of hippocampal volume are low to moderate (Peper et al, 2007;Schmitt et al, 2007) it is possible that the observed hippocampal volume reductions are best explained by environmental rather than genetic influences. In line with such an interpretation are findings from a recent study of 10 MZ twin pairs discordant for the risk of anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33] Behavioral genetic studies have shown that the frontal lobe is under substantial genetic control in healthy humans, with heritability estimates of frontal volumes of approximately 90%. 34,35 What is less clear is the extent to which frontostriatal volume changes in schizophrenia are influenced by the genetic risk for the disorder itself. The subtle yet statistically reliable volumetric changes seen in patients with schizophrenia could reflect the impact of genetic, epigenetic, or environmental factors.…”
Section: Introductionmentioning
confidence: 99%